2013
DOI: 10.1037/a0030530
|View full text |Cite
|
Sign up to set email alerts
|

Does logic feel good? Testing for intuitive detection of logicality in syllogistic reasoning.

Abstract: Recent research on syllogistic reasoning suggests that the logical status (valid vs. invalid) of even difficult syllogisms can be intuitively detected via small changes in affective state (Morsanyi & Handley, 2012). In a series of 6 experiments, we replicated effects of logical status on liking ratings of difficult syllogisms (although their shape differs from that reported by Morsanyi and Handley), and we tested 2 alternative accounts of our and Morsanyi and Handley's findings in terms of surface features acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 16 publications
(27 reference statements)
3
55
0
1
Order By: Relevance
“…This leads us to suppose that the majority of the participants did not perceive the confl ict between the logical validity of the tasks and the professional beliefs and expectations that counterbalanced the negative statements made. Thus, despite the discomfort reported by a small number of individuals, especially those who saw the stories and depreciative content, this confl ict seems to have been implicit in most of the participants, as suggested by the reports of some participants when they were asked their opinion about the task and whether it mobilized them affectively, which is coherent with results of studies in the area (Blanchette & Amato, 2014;Blanchette & Leese, 2011;Klauer & Singmann, 2013), which to a certain extent, corroborate the idea of the prevalence of implicit heuristic processes associated with System 1 of Kahneman's model (2003), when there is a confl ict between logic and emotion. This issue, however, deserves further clarifi cation in complementary studies that use verbal protocols or other self-reporting instruments that can bring more information in this regard.…”
Section: Discussionsupporting
confidence: 82%
“…This leads us to suppose that the majority of the participants did not perceive the confl ict between the logical validity of the tasks and the professional beliefs and expectations that counterbalanced the negative statements made. Thus, despite the discomfort reported by a small number of individuals, especially those who saw the stories and depreciative content, this confl ict seems to have been implicit in most of the participants, as suggested by the reports of some participants when they were asked their opinion about the task and whether it mobilized them affectively, which is coherent with results of studies in the area (Blanchette & Amato, 2014;Blanchette & Leese, 2011;Klauer & Singmann, 2013), which to a certain extent, corroborate the idea of the prevalence of implicit heuristic processes associated with System 1 of Kahneman's model (2003), when there is a confl ict between logic and emotion. This issue, however, deserves further clarifi cation in complementary studies that use verbal protocols or other self-reporting instruments that can bring more information in this regard.…”
Section: Discussionsupporting
confidence: 82%
“…It is possible that there are boundary conditions on the effects that have been found in these earlier experiments, and indeed this possibility has been noted by De Neys (2012;. For instance, it has been demonstrated that participants report "liking" syllogisms which are logically valid more than those which are invalid, even when not asked to evaluate their logical status (Morsanyi & Handley, 2012), but also that this effect only holds for simpler logical forms (Klauer & Singmann, 2013). The operations required to reach the correct answer to our CRT problems are considerably more complex than those needed to evaluate a simple syllogism, or apply basic statistical principles.…”
Section: Discussionmentioning
confidence: 77%
“…Klauer & Singmann, 2013). Some of the particular topics used in the conflict syllogisms may have evoked different processing strategies than the topics used in the no-conflict syllogisms, and these differences in content, rather than the presence of a belief-logic conflict, might have been responsible for the differences found between the conditions.…”
Section: Resultsmentioning
confidence: 98%